Hukum Keluarga Islam di Tengah Arus Globalisasi: Dampak Media Sosial Terhadap Pola Pernikahan dan Relasi Keluarga Muslim: Islamic Family Law in the Midst of Globalization: The Impact of Social Media on Muslim Marriage Patterns and Family Relations - Wahyudi Wahyudi; Oyo Sunaryo Mukhlas; Beni Ahmad Saebani (Fakultas Hukum Universitas Komputer Indonesia, 2025)
This article examines the impact of social media as a primary instrument of globalization on the socio-legal norms of Islamic family law (fiqh al-usrah). It argues that digital platforms have created a new public sphere that significantly transforms the social construction and practice of Islamic marriage and family relations. Using a socio-legal research method that analyzes classical jurisprudence (fiqh) texts, contemporary legal compilations, and empirical phenomena from social media, this study focuses on three critical areas: the transformation of matchmaking (khiṭbah) into a digital